Chloroquine sensitises hypoxic colorectal cancer cells to ROS-mediated cell death via structural disruption of pyruvate dehydrogenase kinase 1 - Mir, Irfan Ahmad; Mir, Hilal Ahmad; Mehraj, Umar; Bhat, Mohd Younus; Mir, Manzoor Ahmad; Dar, Tanveer Ali; Hussain, Mahboob-Ul (Free radical biology & medicine, 2025)
Chloroquine (CQ), an autophagy antagonist, has been recently explored as a repurposable medicine for cancer; however the exact mechanism of its action is still not known. The present study investigated the effect of CQ on colorectal cancer cells to elucidate the underlying molecular mechanisms. We report for the first time that CQ suppresses hypoxia-induced growth and survival of HCT-116 cells by reducing glycolytic capacity and NAD+ production through inhibition of PDK1. Furthermore, in silico and in vitro studies revealed that CQ induces structural alteration in the PDK1 protein, leading to its destabilization and promotes its enhanced degradation by proteases. This degradation is in turn inhibited by the MG-132 protease inhibitor. Moreover, CQ-induced suppression of PDK1 results in mitochondrial damage through excessive production of ROS, as reflected by the reduction in mitochondrial membrane potential, which in turn triggers apoptosis through PARP cleavage and Caspase activation. These findings advocate CQ as a promising repurposable chemotherapeutic for colorectal cancer and a novel inhibitor of PDK1. In absence of Chloroquine-Active PDK1 inhibits activity of pyruvate dehydrogenase complex (PDHC) promoting Warburg effect, which inhibits ROS generation and stimulates cell survival and growth.In presence of Chloroquine –CQ-induced destabilization of PDK1 promotes its degradation, resulting in increased mitochondrial oxidative phosphorylation (OXPHOs) thereby increasing ROS generation and cell death. [Display omitted] •CQ suppresses proliferation of hypoxic HCT-116 cells through the inhibition of anaerobic glycolysis.•This effect of CQ is facilitated by its targeting of PDK1, a kinase crucial for glycolytic reprogramming during hypoxa.•CQ directly binds to PDK1, affecting its overall conformation, stability, and bioavailability.•CQ-mediated loss of PDK1 triggers ROS-dependent apoptosis in HCT-116 cells by reducing mitochondrial activity.